PENGARUH PRAKTIK TOTAL QUALITY MANAGEMENT TERHADAP KINERJA USAHA DAN DAYA SAING SEBAGAI VARIABEL MEDIASI PADA USAHA KECIL DAN MENENGAH DI KOTA DUMAI - Minci, Veronika Yurike; Samsir, Samsir; Paramitha, Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Business performance can be improved by implementating Total Quality Management. Total Quality Management plays a very important role in increasing the strength of the business competitiveness. Good business performance will be able to compete with other businesses in improving the quality of the product. This research aims to determine the effects of Total Quality Management practice to business performance and competitiveness as a mediation variable at small and medium business in Dumai City. Population of this research is small and medium business that produces a typical souvenirs of Riau in Dumai City, totaling 68 bussiness.The sampling technique using census method. Hypothesis testing in this research is using Structural Equation Modeling (SEM) with SmartPLS. The result showed that Total Quality Management practice have positive and significant effect on competitiveness and business performance. Competitiveness have positive and significant effect on business performance and Total Quality Management practice have positive and significant effect on business performance by competitiveness as a mediation variable. Competitiveness in this research is a partial mediation variable.Keywords : Total Quality Management Practice, Business Performance, Competitiveness.